OP0033 Effect of a step-up or step-down in tofacitinib dose on efficacy and safety in patients with rheumatoid arthritis in long-term extension studies. (12th June 2018) - Mueller, R.B.; Schulze-Koops, H.; Furst, D.E.; Cohen, S.; Kwok, K.; Maniccia, A.; Wang, L.; Akylbekova, E.; Ackermann, G.; von Kempis, J.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Efficacy and safety of tofacitinib 5 and 10 mg BID have been shown in long-term extension (LTE) studies up to 114 months. 1 Objectives: To assess the impact of tofacitinib dose changes on efficacy and safety in patients (pts) who increased (step-up) or who decreased (step-down) dose, vs pts who remained on the same dose when entering LTE studies. Methods: In this exploratory, post hoc analysis, data were pooled from 2 open-label LTE studies (NCT00413699 [ongoing; database not locked at Jan 2016 data-cut]; NCT00661661 ) of pts with RA who had participated in Phase (P) 1/2/3 tofacitinib index studies and had ≥81 days of tofacitinib exposure (to allow ≥2 assessments) in each period (P1/2/3 index and LTE). Dose changes from index study dose were mandated by protocol (at LTE entry) or at the investigator's discretion (during LTE). This analysis only included pts who remained on their initial/changed dose in the LTE. Pts were analysed in 4 groups: 5 mg BID [index]→10 mg BID [LTE] (Step-up; n=833); 5 mg BID [index]→5 mg BID [LTE] (Remain 5; n=248); 10 mg BID [index]→10 mg BID [LTE] (Remain 10; n=951); 10 mg BID [index]→5 mg BID [LTE] (Step-down; n=234). To determine if initial efficacy (last index study assessment) affects response following dose change on LTE entry, sub-groups for the Step-up and Remain 5 groups were defined based on initial ACR20 response, and sub-groups for the Step-down and Remain 10 groups were defined based on initial ACR50 response. Efficacy was assessed up to Month 12 in the LTE based on ΔDAS28-4(ESR). Exposure-adjusted event rates (pts with events/100 pt-yrs) are presented for the most common adverse events (AEs) for the entire LTE study exposure. Results: No statistically significant differences in ΔDAS28-4(ESR) were observed between the Step-up and Remain 5 groups (figure 1A), whether or not they had an initial ACR20 response (data not shown). In general, no significant differences in ΔDAS28-4(ESR) were observed between the Step-down and Remain 10 groups (figure 1B), whether or not they had an initial ACR50 response (data not shown). The rates and types of AEs were similar across all groups (table 1). Conclusions: In pts with RA, the safety profile was similar regardless of dose change. Step-up from tofacitinib 5 to 10 mg BID, or step-down from 10 to 5 mg BID, did not affect efficacy over 12 months vs remaining on the same dose, and was not influenced by initial response. Conclusions were limited by small pt numbers in some groups, the open-label design and inclusion of pts in the LTE who showed tolerability for tofacitinib and drug retention. Reference: [1] Wollenhaupt J, et al. Arthritis Rheumatol 2017;69(suppl 10):Abstract 522. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by A MacLachlan of CMC and funded by Pfizer Inc. Disclosure of Interest: R. Mueller: None declared, H. Schulze-Koops: None declared, D. Furst Consultant for: Pfizer Inc, S. Cohen Grant/research support from: AbbVie, Amgen, Astellas, Bristol-Myers Squibb, Eli Lilly, Genentech, Gilead, Janssen, Novartis, Pfizer Inc, Roche, Sandoz, Consultant for: AbbVie, Amgen, Astellas, Bristol-Myers Squibb, Eli Lilly, Genentech, Gilead, Janssen, Novartis, Pfizer Inc, Roche, Sandoz, K. Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Maniccia Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Akylbekova Consultant for: Pfizer Inc, Employee of: IQVIA, G. Ackermann Employee of: Pfizer AG, J. von Kempis: None declared